Group 3 Pulmonary Hypertension: Mechanistic Insights, Clinical Challenges, and Evolving Therapies - Steven C. Liu; Madeline Ku; Priyanka Mohnani; Tanvi Borse; Bharat Bajantri (Journal of Clinical Medicine, 2026)
Group 3 pulmonary hypertension is a common and clinically significant complication of chronic lung disease and hypoxia that is associated with impaired functional capacity, right ventricular dysfunction, and increased mortality. Historically viewed as a consequence of underlying parenchymal lung disease, Group 3 pulmonary hypertension is now recognized as a complex disorder involving pulmonary vascular remodeling, dysregulated molecular signaling, and maladaptive cardiopulmonary interactions. Advances in translational research have improved our understanding of the mechanisms driving disease progression and have informed the development of targeted therapeutic strategies. This review provides an overview of the current understanding of Group 3 pulmonary hypertension, including its pathophysiology, diagnostic evaluation, and evolving treatment landscape. Specifically, this review dives into the reason behind limited therapeutic success, the outcomes of previous clinical trials, and the emergence of lung-selective approaches that seek to balance pulmonary vascular benefit with preservation of gas exchange. Collectively, these developments highlight both the progress made and the ongoing need for improved phenotyping and novel therapeutic approaches in the Group 3 pulmonary hypertension patient population.